TRANSFORMATIONS OF MONA LISA: THE CASE OF A DISTANCE EDUCATION ART-AND-TECHNOLOGY PROJECT (Proceedings of the International Conference on Education, 2021)
Mona Lisa by Leonardo Da Vinci has been subject to numerous and various transformations in the form of (re)interpretations, reproductions, replicas, appropriations and parodies. Mona Lisa is far more than a mere Renaissance portrait or a symbol of its time. Instead Mona Lisa is radically connected with artistic movements and practices throughout the history of art as well as with the 20th and 21st century visual culture, visual commerce and social media imagery. This paper presents an activity in a higher education Department of Early Childhood where students experimented with digital tools and made a collective artwork of digital transformations of Mona Lisa. This digital experiment was a distance education project which took place during the COVID-19 pandemic restrictions in Greece. At first, students were given examples of appropriations and parodies of Mona Lisa from the history of art as well as from the visual culture. Then students gave their own "responses" through making digitally transformed versions of Mona Lisa which they put together in a collective digital mosaic. Clones, distortions, semi-transparencies, repositions and other transformations within 75 Mona Lisa versions render this collective artwork a composition with reference to pixel structure. Students' collective artwork contributed to the deeper understanding of Da Vinci's masterpiece and increased their confidence and familiarity with Renaissance painting. The case of this activity proves that digital culture is a catalyst for art history learning and creativity in the classroom. Furthermore, this activity fosters collaborative learning through distance education and turns out to be a vehicle for empowering learners in a digital world, as well as for developing linguistic, numerical and multisensory skills through digital creativity.
Keywords: Mona Lisa, Leonardo Da Vinci, distance education, higher education, digital art, participatory practices, community resilience